Maximum Length Report of Gonostoma denudatum Rafinesque, 1810 in the Eastern Mediterranean Sea - Deniz Ayas; Hasan Deniz Akbora; Deniz Ergüden (Marine Science and Technology Bulletin, 2020)
The present paper reports the maximum length of the rare seen deep-sea fish bristlemouth Gonostoma denudatum Rafinesque, 1810 in the Mediterranean. One specimen of G. denudatum was caught using a trawler from the deep seas of Northern Cyprus waters on June 22th 2019. The total length (TL) of the specimen was 165 mm, the standard length (SL) was 149.5 mm, and the total weight was 16.2 g. Till today, this sample shown to this species maximum length (TL), which was recorded for the Mediterranean as well as in Eastern basin waters.